Sistem Administrasi PPDB Online di Dinas Pendidikan Kota Denpasar (Studi Kasus: SMP Negeri 3 Denpasar) - Widianingsih, Ni Kadek Candra (CITIZEN CHARTER, 2017)
ABSTRACT The rapid development of technology is now forcing the establishment of a program that is able to answer the problems in the world of education. To answer these problems, the government makes an online New Student Acceptance Program (PPDB). The purpose of this study is to find out the online admission administration of new learners in the Office of Education Youth and Sports of Denpasar City, especially in the Junior High School. Analyzed by the theory of Educational Administration. The implementation of New Student Acceptance in the Office of Education of Youth and Sports of Denpasar especially the implementation in SMPN 3 Denpasar is quite good although in the implementation there are some obstacles that hamper such as lack of socialization. Therefore, the suggestions of this research is the increase, especially in program planning by providing appropriate socialization about the implementation of the program as well. Kata Kunci: new student acceptance, educational administration, online